DARI MUKJIZAT KE KEMISKINAN ABSOLUT: PERLAWANAN PETANI DI RIAU MASA ORDE BARU DAN REFORMASI 1970-2010 - Zaiyardam, Zaiyardam; Lindayanti, Lindayanti (Paramita: Historical Studies Journal, 2017)
The research objective is to learn the unjustice economic policy. It is necessary look for alternative policies that favor the farmers. The research method was qualitative. The method was carried out through a series of interviews with resource persons who understand the problem. In addition, documentary method was used. The research found that the life of the poor peasants are deeply deprived. Their land, field, forest and jungle had been grabbed by the state and the capitalist. After being land grabbed, they serve as slaves and receive small wages which were only sufficient to survive. During the dry season, these slaves were told to burn the land. If caught, the charge falls on them. "Fire is done by the people of Badarai, which performed shifting cultivation," wrote the mass media, which is a mouthpiece for capitalists. If caught, they were left. Without sin, the business owner sent other slaves back to burn the forest in order to clear the land. Exact phrase Pope Francis, the capitalist is dirt of devils. Said it all. However, farmers fight back. The style of resistance like the wind on the high seas. Occasionally breezy. On the other full-time ripples. Sometimes like a hurricane, devastated. Waves of resistances came inexhaustibly with the aim of restoring their land robbed. For robbery, enslavement and burning that they had done, can the state and the capitalists be categorized as a terrorist?. In this context, this paper attempting to give a new perspective on the state and capitalist as terrorists.Â Tujuan penelitian ini adalah untuk mempelajari kebijakan ekonomi ketidakadilan. Hal ini terlihat diperlukan untuk kebijakan alternatif yang menguntungkan petani. Penelitian ini menemukan bahwa kehidupan para petani miskin sangat kehilangan tanah mereka, bidang, hutan dan hutan telah diraih oleh negara dan kapitalis. Setelah tanah menyambar, mereka melayani sebagai budak dan menerima upah kecil yang hanya cukup untuk bertahan hidup. Selama musim kemarau, budak tersebut diberitahu untuk membakar lahan. Jika tertangkap, biaya jatuh pada mereka. "Api yang dilakukan oleh orang-orang dari Badarai, yang dilakukan dengan perladangan berpindah," tulis media massa, yang merupakan corong kapitalis. Jika tertangkap, mereka ditinggalkan. Tanpa dosa, pemilik bisnis menyuruh hamba lain kembali untuk membakar hutan untuk membuka lahan. Frase yang tepat menurut Paus Francis, kapitalis adalah kotoran iblis. Namun, petani melawan. Gaya perlawanan seperti angin di laut lepas. Sesekali semilir, beriak di waktu lainnya. Kadang-kadang seperti badai yang menghancurkan. Gelombang resistensi datang tujuan memulihkan tanah mereka dirampok. Karena perampokan, perbudakan dan pembakaran bahwa mereka telah melakukan, bisa negara dan kapitalis dikategorikan sebagai teroris? Dalam konteks ini, tulisan ini mencoba untuk memberikan perspektif baru tentang negara dan kapitalis sebagai teroris.Â